Energy and economic evaluation of combined sensible-latent thermal energy storage system with various volume fractions of phase change material - Suresh, C.; Awasthi, Abhishek; Lee, Dongchan; Jeon, Yongseok (Alexandria Engineering Journal, 2024)
Thermal energy storage (TES) systems have been verified to be a promising solution for reducing the imbalance between energy supply and demand; however, sensible and latent thermal storage systems have certain limitations. To minimize the issues of rapid drop of temperature in sensible storage and poor heat transfer in latent storage, novel thermal energy storage should be designed. Considering this, combined sensible-latent TES system was developed to mitigate the drawbacks of individual sensible and latent storage. This study aims to investigate experimentally the impact of various volume fractions of phase change material (PCM) in the proposed system on thermal performance and also in terms of economics. The results demonstrated that 60% PCM volume fraction had 50.03% lower capacity cost, 165.4% higher storage capacity, 168.8% higher storage density, and 26.47% efficiency than the sensible TES. Furthermore, 60% volume fraction of PCM had a 13.09% lower installation cost, 4.77% and 11.69% lower charging/discharging time, and 12.64% higher efficiency than the latent storage system. This concludes that under the assumptions of the current study, a 60% volume fraction of PCM is the optimal design parameter for a combined sensible-latent TES system for achieving the best performance in terms of cost and thermal performance.
Keywords: Capacity costs; Capitals costs; Combined thermal energy storage; Concrete; Energy evaluation; Latent storages; Latent thermal energy storages; Thermal energy storage; Thermal energy storage systems; Thermal Performance; Capacity cost; Capital cost; Combined thermal energy storage; Concrete; Phase change material